Pengaruh Green Human Resource Management Terhadap Pro - Enviromental Behavior Dimediasi oleh Green Knowledge Sharing dan Psychological Green Climate pada Karyawan Destinasi Wisata di Kabupaten Bogor - Anggita Agustia; Netania Emilisa; Viona Kayla; Renata Alifia; Zahra Afifah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the effect of Green Human Resource Management (GHRM) on Pro-Environmental Behavior (PEB) mediated by Green Knowledge Sharing (GKS) and Psychological Green Climate (PGC) among employees of tourism destinations in Bogor Regency, Indonesia. This quantitative research employed a correlational approach using a survey method with 220 respondents. The findings reveal that GHRM has a significant positive effect on both GKS and PGC. Furthermore, GKS and PGC positively influence PEB. The study also confirms that GKS and PGC fully mediate the relationship between GHRM and PEB. However, the direct effect of GHRM on PEB shows a negative relationship, indicating that without the support of knowledge-sharing processes and a positive psychological green climate, GHRM practices alone are insufficient to enhance pro-environmental behavior. These findings highlight the importance of strengthening green knowledge-sharing culture and fostering a supportive psychological climate to promote environmentally responsible behavior among tourism employees.